Philosophy of international law - Carty, Anthony (Edinburgh University Press, 2017)
Tracks the development of the foundations of the philosophies of international law, covering the natural, analytical, positivist, realist and postmodern legal traditions. You'll learn how these approaches were first conceived and how they shape the network of relationships between the signatories of international law --Source other than the Library of Congress.